The Effect of Intellectual Capital and Debt to Equity Ratio on Company Value with Company Size as a Moderation Variable in Technology Companies Listed on the Indonesia Stock Exchange for the 2020-2023 Period - Eka Fitriatul Afifah; Marista Oktaviani; Nurullaili Mauliddah (P3I UMSurabaya, 2025)
This study aims to analyze the influence of Intellectual Capital and Debt to Equity Ratio (DER) on company value, as well as the role of company size as a moderation variable in technology companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The research method used is quantitative associative with secondary data obtained from the company's annual report. The sample consisted of 15 technology companies selected through the purposive sampling method, resulting in a total of 60 observational data. The analysis technique used was panel data regression with the Moderated Regression Analysis (MRA) approach using the EViews 12 statistical test tool. The results of the study show that Intellectual Capital has a significant positive effect on the value of the company. The Debt to Equity Ratio also has a significant positive influence on the value of the company. However, the size of the company is not able to moderate the relationship between Intellectual Capital and the value of the company. On the other hand, the size of the company has been proven to moderate the influence of the Debt to Equity Ratio on the value of the company. The value of the determination coefficient (R2) of 0.998320 indicates that the variation in the company's value can be explained by 99.83% by independent variables in the model. These findings show that the management of intangible assets such as Intellectual Capital as well as capital structures through DER have an important role in increasing the value of companies. However, the scale of the company does not always reinforce that influence consistently.